2016
DOI: 10.1371/journal.pntd.0004515
|View full text |Cite
|
Sign up to set email alerts
|

School Water, Sanitation, and Hygiene, Soil-Transmitted Helminths, and Schistosomes: National Mapping in Ethiopia

Abstract: BackgroundIt is thought that improving water, sanitation, and hygiene (WASH) might reduce the transmission of schistosomes and soil-transmitted helminths, owing to their life cycles. However, few large-scale studies have yet assessed the real extent of associations between WASH and these parasites.Methodology/Principal FindingsIn the 2013–2014 Ethiopian national mapping of infections with these parasites, school WASH was assessed alongside infection intensity in children, mostly between 10 and 15 years of age.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 30 publications
(46 reference statements)
5
56
3
2
Order By: Relevance
“…Compared with the 24.6% prevalence found in Ethiopia (16), 26.3% in the Democratic Republic of Congo, and 26.5% found in Kenya (47, 48), we found a higher prevalence of T. trichiura infection. Our findings also revealed higher rates of A. lumbricoides infection compared with rates of 10.6% to 13% in other areas of southern Ethiopia (12, 49). The rate for hookworm infection in this study aligned with the 7.4% rate found during national mapping (49).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Compared with the 24.6% prevalence found in Ethiopia (16), 26.3% in the Democratic Republic of Congo, and 26.5% found in Kenya (47, 48), we found a higher prevalence of T. trichiura infection. Our findings also revealed higher rates of A. lumbricoides infection compared with rates of 10.6% to 13% in other areas of southern Ethiopia (12, 49). The rate for hookworm infection in this study aligned with the 7.4% rate found during national mapping (49).…”
Section: Discussionsupporting
confidence: 66%
“…Our findings also revealed higher rates of A. lumbricoides infection compared with rates of 10.6% to 13% in other areas of southern Ethiopia (12, 49). The rate for hookworm infection in this study aligned with the 7.4% rate found during national mapping (49). However, it is lower than the 56.8% (16), 46.9% (50), and 18% reported in other regions of Ethiopia (24).…”
Section: Discussionsupporting
confidence: 66%
“…In addition, a questionnaire was conducted to collect information on water, sanitation and hygiene (WASH) at the school level. The results of this questionnaire and parasite infection for the rst round of survey were reported elsewhere by Grimes et al [21].…”
Section: Field Proceduresmentioning
confidence: 80%
“…Further, there were missing studies in the literature on malaria with links to LULC in 2016 and 2017. It was identified that studies on hookworm were found only in 2016 [66].…”
Section: Identified Water-related Infectious Diseasesmentioning
confidence: 99%